Multi-Epitope DC Vaccines with Melanoma Antigens for Immunotherapy of Melanoma - Seretis, Athanasios; Amon, Lukas; Tripp, Christoph H.; Cappellano, Giuseppe; Hornsteiner, Florian; Dieckmann, Sophie; Vierthaler, Janine; Ortner-Tobider, Daniela; Kanduth, Markus; Steindl, Rita; Boon, Louis; den Haan, Joke M.M.; et al. (Vaccines, 2025)
Background/Objectives: The revolution for the treatment of melanoma came with the approval of checkpoint blockade antibodies. However, a substantial proportion of patients show primary or secondary resistance to this type of immunotherapy, indicating the need for alternative therapeutic strategies. Dendritic cells (DCs) of the skin are prime targets for vaccination approaches due to their potential to prime naïve T cells and their accessibility. This study aimed to develop and evaluate novel vaccines targeting the C-type lectin receptor DEC-205 to deliver melanoma-associated antigenic peptides to skin DCs. Methods: We cloned MHC-I-restricted peptides from the glycoprotein (gp)10025–33 and Tyrosinase-related protein (trp)2180–188 into the DEC-205 antibody sequence with modified peptide cutting sites from the OVA257–264 SIINFEKL peptide. We tested their potential to induce CD8+ T cell responses in both in vitro and in vivo settings. Tumor growth inhibition was evaluated in the transplantable B16.OVA melanoma murine model using a multi-epitope DC-based vaccine combining both peptides. Results: The cross-presentation of both gp100 and trp2 peptides was confirmed in vivo when peptide sequences were flanked by the OVA257–264 peptide cutting sites. Moreover, the combination of both antigenic peptides into a multi-epitope DC vaccine was required to inhibit B16.OVA melanoma growth. Conclusions: Our findings suggest that a DC-targeted vaccination approach using multiple epitopes deriving from melanoma antigens could represent a promising strategy for melanoma therapy.
CRIS-Team Scopus Importer:2025-05-09
Keywords: C-type lectin receptors; DC-targeted therapy; dendritic cells; immunotherapy; melanoma antigens